2006
DOI: 10.1521/bumc.2006.70.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Organization and Dissociation

Abstract: The relationship between Kernberg's psychodynamic model of personality organization (PO) and dissociation has not yet been explored. Seventy-two nonclinical subjects and 222 psychiatric patients completed the Dissociative Experiences Scale and the Inventory of Personality Organization. Its Reality Testing subscale emerged as the most important predictor for all facets of dissociation. Discussing our results in the framework of Fonagy and coworkers' model of mentalization, we suggest that dissociation may refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Furthermore, the IPO appeared to be sensitive to changes in aspects of borderline personality organization following psychotherapeutic treatment (Arntz & Bernstein, 2006). Finally, the RT subscale emerged as a predictor for different facets of dissociation (Spitzer et al, 2006).…”
Section: Bulletin Of the Menninger Clinicmentioning
confidence: 94%
“…Furthermore, the IPO appeared to be sensitive to changes in aspects of borderline personality organization following psychotherapeutic treatment (Arntz & Bernstein, 2006). Finally, the RT subscale emerged as a predictor for different facets of dissociation (Spitzer et al, 2006).…”
Section: Bulletin Of the Menninger Clinicmentioning
confidence: 94%
“…Numerous investigations established the close link between BPD and dissociation. 50 53 Chronic and complex dissociative symptoms are common. 51 , 52 , 54 56 Dissociation is understood as a coping strategy to deal with tough, stressful circumstances, and with hurtful trauma experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The IPO has also shown theoretically appropriate correlations with other problematic personality traits and psychiatric symptoms. For example, the Impaired Reality Testing subscale has been shown to be a good predictor of dissociative symptoms among both psychiatric patients and nonclinical controls (Spitzer et al, 2006), and Pincus et al (2009), using a nonclinical undergraduate sample, found that IPO subscales were highly correlated with pathological narcissism, a personality style typically associated with a borderline personality organization in Kernberg's model. In addition, the IPO has been used to assess structural change in personality as a psychotherapy outcome among individuals with BPD (Arntz & Bernstein, 2006; Giesen-Bloo et al, 2006).…”
mentioning
confidence: 99%